2006
DOI: 10.1128/aac.00747-06
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis for Enhanced Activity of Posaconazole against Absidia corymbifera and Rhizopus oryzae

Abstract: Posaconazole and itraconazole were more potent inhibitors of ergosterol synthesis, in both intact cells and cell extracts from Absidia corymbifera and Rhizopus oryzae, than voriconazole and fluconazole. Similarly, expression of CYP51 from R. oryzae in Saccharomyces cerevisiae significantly increased resistance to fluconazole and voriconazole but not to posaconazole and itraconazole.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 16 publications
1
20
0
Order By: Relevance
“…Posaconazole is frequently used off-label for the treatment of other documented mold infections, including invasive mucormycosis, when therapeutic options are limited. The enhanced potency of posaconazole against species of the order Mucorales relative to those of other triazoles may be explained, in part, by an increased affinity for fungal P450 demethylase (CYP51) and increased penetration or reduced efflux from the fungal cell membrane (1,2). Consequently, posaconazole MICs for Mucor, Rhizopus, Absidia, and Cunninghamella spp.…”
mentioning
confidence: 99%
“…Posaconazole is frequently used off-label for the treatment of other documented mold infections, including invasive mucormycosis, when therapeutic options are limited. The enhanced potency of posaconazole against species of the order Mucorales relative to those of other triazoles may be explained, in part, by an increased affinity for fungal P450 demethylase (CYP51) and increased penetration or reduced efflux from the fungal cell membrane (1,2). Consequently, posaconazole MICs for Mucor, Rhizopus, Absidia, and Cunninghamella spp.…”
mentioning
confidence: 99%
“…In agreement with this finding, Sheng et al [55] using the C. neoformans Cyp51 model showed that the higher affinity of voriconazole for the protein may be due to an extra hydrophobic interaction with the phenyl group of Y131. Moreover, substitutions in the regions surrounding residue F134 have also been related to voriconazole resistance shown by Absidia corymbifera and Rhizopus oryzae [62].…”
Section: Discussionmentioning
confidence: 99%
“…These are summarised in Table 1 and show a range of minimum inhibitory concentrations (MICs) between ≤0.016 mg/L and > 16 mg/L [6][7][8][9][10][11].…”
Section: Antifungal Susceptibility Datamentioning
confidence: 99%
“…Posaconazole (PCZ) is an orally administered, extended-spectrum triazole antifungal agent with activity against the Mucorales [5]. It is thought to be more active against the Mucorales than voriconazole, another broad-spectrum agent in the group, owing to a combination of increased affinity for the target site coupled with enhanced cellular penetration and/or reduced efflux [6]. This review describes the clinical and laboratory data supporting the use of PCZ against this rare group of pathogens.…”
Section: Introductionmentioning
confidence: 96%